The Influence of Environmental Performance and Profitability on Company Value (An Empirical Study of the Energy Sector Listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 Period) - Aura Putri Azzahra; Rendi Kusuma Natita (JURNAL ECONOMINA, 2026)
The value of companies in the energy sector during the 2020– 2024 period showed fluctuating conditions even though some companies obtained good environmental performance ratings and relatively high levels of profitability. This condition indicates that improvements in environmental performance and profitability have not always been followed by an increase in company value, thus creating uncertainty regarding the influence of these two variables on company value. This researcher aims to determine and analyze the influence of Environmental Performance and Profitability on Company Value. The objects of this study are Energy companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. Environmental Performance in this study was measured using the company performance rating program in environmental management (PROPER), Profitability was measured using Return On Assets (ROA). Company Value was measured using Tobin's Q. The data collection method used purposive sampling . The research sample was 10 companies with 50 sample data. The data analysis technique used was Multiple Linear Regression using IBM SPSS version 27. The results of this study indicate that Environmental Performance has no positive effect on Company Value, Profitability has a positive effect on Company Value, Environmental Performance and Profitability simultaneously affect Company Value.